HUBUNGAN JUMLAH TENAGA KERJA DAN LUAS LAHAN TERHADAP PENDAPATAN PETANI KARET DI KABUPATEN KUTAI KARTANEGARA - AR LINA (Jurnal Ilmu Ekonomi Mulawarman (JIEM), 2016)
The purpose of this study was to prove whether or not relationship between the independent variable (labor and land) to the dependent variable (income) rubber farmers in Kutai Kartanegara Regency. The analytical tool used in this study are Chi-Square using research data directly to farmers in the test with SPSS (Statistical Product and Service Solutions) version 20. From the analysis that I did state that labor and land has a significant relationship to the income of rubber farmers in Kutai Kartanegara Regency.Keywords: Labor, Land and Income